2015
DOI: 10.1007/s00520-015-2844-0
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of amino-acid-rich elemental diet Elental® on chemotherapy-induced oral mucositis in patients with colorectal cancer: a prospective pilot study

Abstract: Purpose The prospective pilot study was designed to evaluate the preventive effects of amino-acid-rich elemental diet (ED), Elental ® , on chemotherapy-induced oral mucositis in patients with colorectal cancer. The factors influencing its efficacy are also investigated. Methods A total of 22 eligible patients with colorectal cancer experiencing grade 1–3 oral mucositis during treatment with fluorouracil-based chemotherapy entered the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Current studies have shown that amino acids themselves can protect the mucosa and have anti-inflammatory effects [ 18 , 26 ]. The administration of an ED during cancer chemotherapy has been reported to have the potential prevent OM [ 17 , 21 ]. Chemotherapy damages DNA through the production of reactive oxygen species, the induction of apoptosis through the upregulation of the expression of intracellular molecules, and the production of several cytokines, such as IL-1β, IL-6, and TNF-α [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies have shown that amino acids themselves can protect the mucosa and have anti-inflammatory effects [ 18 , 26 ]. The administration of an ED during cancer chemotherapy has been reported to have the potential prevent OM [ 17 , 21 ]. Chemotherapy damages DNA through the production of reactive oxygen species, the induction of apoptosis through the upregulation of the expression of intracellular molecules, and the production of several cytokines, such as IL-1β, IL-6, and TNF-α [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Ogata et al’s report [ 21 ], the setting dose of an ED during chemotherapy for colon cancer was 1 pack (80 g)/day, but the average amount of the ED that was able to be taken was 51.7%. This study is a triplet regimen for esophageal cancer, so the setting dose of an ED is 2 packs (160 g)/day.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who received at least one dose of azulene or Elental were included in the analyses. Based on the results of previous studies (28)(29)(30), the difference between the incidences of oral mucositis for two arms was assumed to be 35% (the incidence for the azulene arm and Elental Arm being 50 and 15%, respectively). with one-sided type I error=0.1 and type II error=0.2, it was necessary to include 16 patients in each arm.…”
Section: Assessmentmentioning
confidence: 99%
“…The incidence of grade ≥ 2 OM was the highest in the glutamine group, followed by the control group, and the least in the glutamine plus ED group (p = 0.04). ED was found to be effective also in a cohort study of 22 colorectal cancer patients treated with 5-fluorouracil (FU)-based chemotherapy [60].…”
Section: Elemental Diet (Po): Solid Cancers Ct-prevention Guideline:mentioning
confidence: 99%